FORMULATION AND EVALUATION OF GASTRORETENTIVE FLOATING TABLETS OF LAFUTIDINE - Dolas, Ramdas T.; Sharma, Shalindra; Sharma, Madhuraj (Journal of Drug Delivery and Therapeutics, 2018)
The purpose of this research was to develop a novel gastroretentive drug delivery system based on wet granulation technique for sustained delivery of active agent. Quick GI transit could result in incomplete drug release from the drug delivery system above the absorption zone leading to decreased efficacy of the administered dose and thus less patient compliance. Gastroretentive floating tablets, which was designed to provide the desired sustained and complete release of drug for prolonged period of time. Gastroretentive floating tablets of lafutidine were prepared by wet granulation technique using different concentrations of Gum Kondagagu, Gum olibanum and Locust bean Gum. The optimized formulation (LF14) exhibited 99.54% drug release in 12 hrs, while the buoyancy lag time was 33 sec. In-vitro drug release kinetics was found to follow both the Zero order and the possible mechanism of lafutidine release from the optimized formulation might be attributed to super case II transport mechanism. The Optimized formulation (LF14) showed no significant change in physical appearance, drug content, floating lag time, in vitro dissolution studies after 75%±5% RH at 40±20C relative humidity for 6 months. Keyword: Wet granulation, Floating lag Time, Gastroretentive, Lafutidine